Choosing the new normal for surgical education using alternative platforms (2020)
The traditional methods for surgical education and professional development are changing, from a variety of external factors. The COVID-19 pandemic accelerated the pace innovative alternative tools are introduced into clinical practice, creating a new normal for teaching and training. In this new normal is the challenge to create durable changes for the future of surgical education. Social media (SoMe), a tool that uses electronic communications and applications to allow users create and share information in dynamic ways, can meet this challenge. SoMe is reshaping how we communicate and learn, and offers great benefits for effective, individualized surgical education. The limits for SoMe appear endless, and elements have already help establish digital surgery to help improve the precision and outcomes of surgery. As we work to define the new normal in surgical education and professional development, SoMe digital surgery will be critical for continued growth and progress.